Buya Hamka: Tokoh Modernis Karismatik - Shobahussurur Amir (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2009)
This paper analyzes Hanika by measuring his productivity. Someone who has never formally attended school, but able to write a lot of things. Hamka writes about the history, interpretation, Hadith, Sufism, language, and literature. His work presents an active response from the condition that occurs in society. as urban communities facing extreme Sufism understanding dealing with the secular lifestyle hedonist, he writes Tasawuf Modern. When acute phenomenon feud between indigenous and religion, he writes Tenggelamnya Kapal Van Der Wijck. As modern society away from religion following the materialistic life, he writes Di Bawah Lindungan Ka’bah. His Responses to the condition of society is also expressed as being reflected in the prison, to be born monumental works; Tafsir Al-Azhar.